Sustainability and Traditional Urban Tissue Baghdad House as case study - Al Dabbagh, Jassim A. (Nahrain University College of Engineering Journal, 2017)
In this day and age "Sustainability" is considered the topic of the hour from a developmental, environmental, social and economical point of view. And from the end of the 1980s due to the climatical changes the concept of architectural and building sustainability appeared as a new idiom …..Nowadays there are many architectural as well as urban projects approved according to sustainability criteria as it is a huge challenge to deal with the serious dangers that cities all over the world are facing. On the other hand we are still mesmerized by the tall glass towers and skyscrapers that spend a lot of energy and create psychologically unpleasant spaces. Unfortunately today the decorative and artificial finishing’s dominate the buildings elevations, while our architectural heritage is being neglected .The research focuses on combining between hereditary architecture which does not depend on energy and sustainable architecture which is based on renewable energy instead of depilatory energy whenever possible. The main goal of this research is to recognize how the sustainable architectural criteria in the modern and urban environment with the outputs of hereditary architect will help to produce sustainable local architecture.